Increased Levels of Plasma Extracellular Heat-Shock Proteins 60 and 70 kDa Characterized Early-Onset Neonatal Sepsis - Canul-Euan, Arturo Alejandro; Zúñiga-González, Gibran; Palacios-Luna, Janelly Estefania; Maida-Claros, Rolando; Díaz, Néstor Fabián; Saltigeral-Tigeral, Patricia; Karina García-May, Perla; Díaz-Ruiz, Oscar; Flores-Herrera, Héctor (Frontiers in Pediatrics, 2021)
Background: Extracellular heat-shock proteins (eHsp) a highly conserved molecules that play an important role in inflammatory diseases and have been quantified in serum from patients with infectious diseases, including sepsis. There is a constant search for dependable biochemical markers that, in combination with conventional methods, could deliver a prompt and reliable diagnosis of early-onset neonatal sepsis. Objective: We sought to assess the level of eHsp-27, -60, -70, and TNFα in serum of healthy neonates at term and infants with early-onset neonatal sepsis. Methods: This study included 34 newborns were classified as healthy neonates at term (blood samples from the umbilical cord at birth; n=23) or infants with early-neonatal sepsis (blood samples obtained by standard sterile procedures before starting a systemic antibiotic intervention; n=11). All blood samples were centrifuged, and the serum recovered to determine eHsp-27, -60, -70 and TNFα levels by ELISA. Results: Our results indicate that the level of eHsp-27 in healthy neonates at term was 0.045 ± 0.024 pg/mL. This value decreased 2.5-fold in infants with early-onset neonate sepsis (0.019 ± 0.006 pg/mL, p =0.004). In contrast, the levels of eHsp-60 and -70 in healthy neonates at term were 13.69 ± 5.3 pg/ml and 4.03 ± 2.6 pg/ml, respectively. These protein levels increased significantly 1.8- and 1.9-fold in the serum of infants with early-onset neonatal sepsis (p ≤0.001, table 5). The level of TNFα in healthy neonates at term was 2.94 ± 0.46 pg/ml, with a 3.0-fold increase in infants with early-onset neonatal sepsis (8.96 ± 0.72 pm/ml, p ≤0.001, table 5). The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for eHsp compared to C-reactive protein were 73.3%, 60.0%, 47.8% and 33.3%, respectively. Conclusion: This study demonstrated a consistent increase of eHsp-60, -70 in the serum of infants diagnosed with early-onset neonatal sepsis. These proteins showed higher sensitivity and specificity than C-reactive protein and blood culture test.